A copula approach to modelling dependence structures between Asian equity markets. - Chin, Zhuo Song. (2011)
In recent times, increased dependence between markets and asset classes has rendered traditional techniques such as linear correlation incapable of adequately modelling dependence structures. This has led to growing interest amongst academics and portfolio managers in new and more effective tools to analyse inter-market and inter-asset dependences.